Smart releasing electrospun nanofibers—poly: L.lactide fibers as dual drug delivery system for biomedical application. (11th December 2020) - Wulf, Katharina; Arbeiter, Daniela; Matschegewski, Claudia; Teske, Michael; Huling, Jennifer; Schmitz, Klaus-Peter; Grabow, Niels; Kohse, Stefanie
Abstract: An ongoing challenge in drug delivery systems for a variety of medical applications, including cardiovascular diseases, is the delivery of multiple drugs to address numerous phases of a treatment or healing process. Therefore, an extended dual drug delivery system (DDDS) based on our previously reported cardiac DDDS was generated. Here we use the polymer poly(L-lactide) (PLLA) as drug carrier with the cytostatic drug Paclitaxel (PTX) and the endothelial cell proliferation enhancing growth factor, human vascular endothelial growth factor (VEGF), to overcome typical in-stent restenosis complications. We succeeded in using one solution to generate two separate DDDS via spray coating (film) and electrospinning (nonwoven) with the same content of PTX and the same post processing for VEGF immobilisation. Both processes are suitable as coating techniques for implants. The contact angle analysis revealed differences between films and nonwovens. Whereas, the morphological analysis demonstrated nearly no changes occurred after immobilisation of both drugs. Glass transition temperatures ( Tg ) and degree of crystallinity (χ) show only minor changes. The amount of immobilised VEGF on nonwovens was over 300% higher compared to the films. Also, the nonwovens revealed a much faster and over three times higher PTX release over 70 d compared to the films. The almost equal physical properties of nonwovens and films allow the comparison of both DDDS independently of their fabrication process. Both films and nonwovens have significantly increased in vitro cell viability for human umbilical vein endothelial cells (EA.hy926) with dual loaded PTX and VEGF compared to PTX-only loaded samples.